VD_FINDINFO Arrêt / 2011 / 827 vom 24. Juni 2011 - VD Tribunal cantonal (2011)
ÉVALUATION DE L'INVALIDITÉ, REVENU D'INVALIDE, LIBRE APPRÉCIATION DES PREUVES | 28 al. 2 LAI, 16 LPGA, 61 let. c LPGA, 27 RAI, 27bis RAI